Distinct Contributions of Autophagy Receptors in Measles Virus Replication - Petkova, Denitsa S. (Viruses, 2017)
Autophagy is a potent cell autonomous defense mechanism that engages the lysosomal pathway to fight intracellular pathogens. Several autophagy receptors can recognize invading pathogens in order to target them towards autophagy for their degradation after the fusion of pathogen-containing autophagosomes with lysosomes. However, numerous intracellular pathogens can avoid or exploit autophagy, among which is measles virus (MeV). This virus induces a complete autophagy flux, which is required to improve viral replication. We therefore asked how measles virus interferes with autophagy receptors during the course of infection. We report that in addition to NDP52/CALCOCO(2) and OPTINEURIN/OPTN, another autophagy receptor, namely T6BP/TAXIBP1, also regulates the maturation of autophagosomes by promoting their fusion with lysosomes, independently of any infection. Surprisingly, only two of these receptors, NDP52 and T6BP, impacted measles virus replication, although independently, and possibly through physical interaction with MeV proteins. Thus, our results suggest that a restricted set of autophagosomes is selectively exploited by measles virus to replicate in the course of infection.